Spatial heterogeneity of four‐dimensional relative pressure fields in the human left ventricle. Issue 6 (26th November 2014) - Eriksson, Jonatan; Bolger, Ann F.; Carlhäll, Carl‐Johan; Ebbers, Tino
Abstract : Purpose: To assess the spatial heterogeneity of the four‐dimensional (4D) relative pressure fields in the healthy human left ventricle (LV) and provide reference data for normal LV relative pressure. Methods: Twelve healthy subjects underwent a cardiac MRI examination where 4D flow and morphological data were acquired. The latter data were segmented and used to define the borders of the LV for computation of relative pressure fields using the pressure Poisson equation. The LV lumen was divided into 17 pie‐shaped segments. Results: In the normal left ventricle, the relative pressure in the apical segments was significantly higher relative to the basal segments ( P  < 0.0005) along both the anteroseptal and inferolateral sides after the peaks of early (E‐wave) and late (A‐wave) diastolic filling. The basal anteroseptal segment showed significantly lower median pressure than the opposite basal inferolateral segment during both E‐wave ( P  < 0.0005) and A‐wave ( P  = 0.0024). Conclusion: Relative pressure in the left ventricle is heterogeneous. During diastole, the main pressure differences in the LV occur along the basal–apical axis. However, pressure differences were also found in the short axis direction and may reflect important aspects of atrioventricular coupling. Additionally, this study provides reference data on LV pressure dynamics for a group of healthy subjects. Magn Reson Med 74:1716–1725, 2015. © 2014 Wiley Periodicals, Inc.